Rapid detection of the invasive tomato leaf miner, Phthorimaea absoluta using simple template LAMP assay - Arindam Kumar; Damini Diksha; Susheel Kumar Sharma; P. R. Shashank; D. Nandhini; Soham Ray; Nitika Gupta; Mukesh Kumar Dhillon (Scientific Reports)
Abstract The tomato leaf miner (TLM), Phthorimaea absoluta Meyrick, 1917 (Lepidoptera: Gelechiidae) is a destructive invasive insect that has expanded its global distribution. Rapid and accurate identification of invasive pests is essential to support subsequent management and devise control measures. To accurately diagnose P. absoluta, a Loop Mediated Isothermal Amplification (LAMP) assay (TLM-LAMP) was developed to amplify the target region of mitochondrial cytochrome oxidase subunit I (COI) gene. The TLM-LAMP assay can identify the P. absoluta within 60 min at 65 °C after sample extraction. Cross-reactivity analysis against three closely related non-target species, Phthorimaea operculella (Zeller, 1873), Pectinophora gossypiella (Saunders, 1844), and Aproaerema modicella (Deventer, 1904) confirmed species specificity. The TLM-LAMP assay showed high sensitivity to P. absoluta DNA up to 1 × 10− 8 ng/µL and in plasmid DNA template up to 1 × 10–14 ng/µL. In addition, the TLM-LAMP assay was successful in laboratory detection of larvae, pupa, and adult stages of P. absoluta. We have tested the TLM-LAMP assay for field application with quick and simple crude insect extraction procedures and found double distilled water (ddH2O) as an effective extraction solution. The new TLM-LAMP assay was validated in the field and polyhouse using moths collected from pheromone traps followed by ddH2O crude insect extract preparation and incubation. The assay could successfully detect the P. absoluta within 45 min at 65 °C. Sensitivity, specificity, repeatability, and field compatibility of the TLM-LAMP highlights the novelty of the developed method. TLM-LAMP assay is a novel molecular tool for detection of P. absoluta in the laboratory and field which will help in monitoring and aiding biosecurity responses.